Operating Systems. A concept-based approach, Second Edition : D.M. Dhamdhere, McGraw Hill, 2006. ISBN 0070611947 - Romero, Fernando (2009)
The book deals with the topic of Operating Systems from and intuitive perspective and then delves into more technical concepts, which makes it appropriate for a first introductory course on the matter.